The Influence of Product Quality and Price on Customer Satisfaction at By Badjua Coffee Shop in Makassar City - Andi Irfan Halim; Andi Jam'an; Samsul Rizal (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
The purpose of this study is to determine the influence of product quality and price on customer satisfaction at By Badjua Coffee Shop in Makassar City. The population of this study consists of 70 individuals. The sampling technique used is saturated sampling. The type of data used in this research is primary data, and the analysis was conducted using SPSS for Windows. Based on the results of the statistical tests, it is evident that individually (partially), the variables of product quality and price have a positive and significant influence on the dependent variable. The influence of these two independent variables is positive, meaning that the higher the level of product quality and price (perceived positively), the higher the resulting customer satisfaction. The findings show that product quality has a significant positive effect on customer satisfaction, and price also has a significant positive effect on customer satisfaction at By Badjua Coffee Shop in Makassar City. It is therefore necessary to continue improving product quality to enhance customer satisfaction at By Badjua Coffee Shop in Makassar City. This research is important because customer satisfaction is a critical factor for business sustainability and competitiveness, especially in the highly competitive coffee shop industry. Understanding the role of product quality and pricing in shaping customer satisfaction can help businesses develop more effective strategies to retain loyal customers and attract new ones, thus ensuring long-term growth and success.